Injeksi Ekstrak Pituitari Sapi pada Ayam Ras Petelur Isa Brown Terhadap Produksi Telur dan Berat Folikel - Pranatasari, Dewi; Lestari, Ipna Siti; Astuti, Yulia; Riyadi, (Journal Galung Tropika, 2025)
This study aims to determine whether the injection of bovine pituitary extract can increase egg production and follicle weight in Isa Brown strain laying hens. This research was conducted from March to May 2024 at Teaching Factory of Poultry Production and Various Livestock and Laboratory of Animal Health and Animal Reproduction of Agricultural Development Polytechnic of Yogyakarta Magelang. The experimental design in this study was a completely randomized design (CRD) with three treatments and six repetitions with four chickens per treatment group. Data were analyzed using analysis of variance (Anova). Treatments that showed a significant effect were continued with Duncan's multiple range test (DMRT). A total of 72 female Isa Brown strain laying hens were divided into three treatments as follows: P0 without bovine pituitary extract injection, P1 bovine pituitary extract injection 0.1 ml/head, and P2 bovine pituitary extract injection 0.2 ml/head. The observed variables were egg production and follicle weight. The result of this study was that the injection of bovine pituitary extract had a significant effect (P<0.05) on egg production and follicle weight. It was concluded that the injection of bovine pituitary extract as much as 0.2 ml/head could increase egg production, while the follicle weight could increase at the injection of bovine pituitary extract as much as 0.1 ml/head.